Robert H. Barlow Through The Archive: to Reveal, Reconstruct and Reify the Historical Traces of a Silenced Life - Clementina Battcock (Globus et Locus, 2021)
During the last years, Mexican academies and institutions focused their activities in preserving and studying the valuable sources of the history of the Country, kept mainly in its archives. Scholars from different places got interested in organize and catalogue all these heterogeneous sources. This article raises the possibility of reconstructing the figure of Robert H. Barlow from the documents contained in five institutional archives in Mexico: the Historical Archive “José Raúl Hellmer Pickman” of the National School of Anthropology and History, the Historical Archive of the Institute of Historical Research of UNAM, the archive of the Mexican Society of Anthropology, the General Archive of the Nation and the National Newspaper Archive of Mexico. Such a task implies considerable challenges since the archive, understood as a privileged instrument of historical memory, confronts us with intricate dynamics of selection, transmission or omission of information, problems that have already been raised by Jacques Derrida, and others, in his book Archive fever. In this sense, the study of Barlow’s figure through documentary repositories allows us to glimpse two vital mdimensions of the American-born researcher: the “academic Barlow” and the “human Barlow”.